2019
DOI: 10.1108/ijwbr-09-2018-0049
|View full text |Cite
|
Sign up to set email alerts
|

What about the environment?

Abstract: Purpose Fungus-resistant grape varieties (FRGVs) are the key to more environment-friendly wine growing. This paper aims to examine whether German consumers are willing to buy environment-friendly wines. The study focuses on reducing the amount of fungicides applied and the improvement of the carbon footprint, which are both related to the FRGVs . Furthermore, a cluster analysis leads to more insights into the consumer groups that are open to environment-friendly wine. Design/methodology/approach A choice exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This statistical technique, which allows groups of firms with homogeneous behaviors to be identified, has been widely used in the management literature in order to generate strategic typologies in different sectors of activity [27]. It is still widely used today [28][29][30]. Indeed, a recent work on the environmental behavior of SMEs in the wine sector opted for this statistical technique [1].…”
Section: Introductionmentioning
confidence: 99%
“…This statistical technique, which allows groups of firms with homogeneous behaviors to be identified, has been widely used in the management literature in order to generate strategic typologies in different sectors of activity [27]. It is still widely used today [28][29][30]. Indeed, a recent work on the environmental behavior of SMEs in the wine sector opted for this statistical technique [1].…”
Section: Introductionmentioning
confidence: 99%
“…This development goes along with stronger emphasis on short supply chains in European agriculture and policy (e.g., Aubry & Kebir, 2013; Chiffoleau, Millet‐Amrani, Rossi, Rivera‐Ferre, & Merino, 2019). Here also the use of specific ‘low pesticide’ wine production labels could be promising (Nesselhauf et al, 2019). Along these lines, the integration of fungus‐resistant varieties into existing labeling structures, such as for the appellation of origin shall have priority.…”
Section: Discussionmentioning
confidence: 99%
“…However, results from taste testing do not necessarily translate into wine sales. Previous studies found consumers are willing to pay less for varieties they are not familiar with which is likely the case for many fungus‐resistant varieties (Nesselhauf, Fleuchaus, & Theuvsen, 2019). In contrast, Vecchio, Pomarici, Giampietri, and Borrello (2022) found consumers were willing to pay more for fungus‐resistant wine than conventional (i.e., from non fungus‐resistant varieties) wine on informal occasions while on formal occasions there was no difference in willingness to pay for fungus‐resistant and conventional wine.…”
Section: Adoption Of Fungus‐resistant Grapevine Varieties and Marketi...mentioning
confidence: 99%
“…A later study of wine consumers in Germany found that price was the most important point for consumers when selecting a wine, with grape cultivar coming second. They also noted that the environmental credentials of DRHGCs, specifically the reduction in pesticide usage and carbon emissions associated with their production, could offset any disadvantage caused by consumer unfamiliarity (Nesselhauf et al., 2019).…”
Section: Advantages and Disadvantages Of Hybrid Grapes For Wine Produ...mentioning
confidence: 99%
“…This paper summarizes the current literature on the chemistry of DRHGCs and on the adaptation of winemaking methods to suit the production of high‐quality wine from DRHGCs. Resistance from consumers, producers, and wholesale buyers has been noted, but this is something that can be overcome with appropriate education (Fuentes Espinoza et al., 2018; Nesselhauf et al., 2019), as is discussed in Section 2.3. Nonetheless, it is suggested that DRHGCs have great potential for the production of high‐quality wines in a sustainable manner.…”
Section: Introductionmentioning
confidence: 99%